Freedom of choice: John Stuart Mill and the tree of life - Jorge Alcalde-Unzu; Miguel A. Ballester; Jorge Nieto (SERIEs - Journal of the Spanish Economic Association, 2012)
This essay deals with the notion and content of freedom of choice proposing a new set up and a new family of measures for this concept which is, indeed, an ethical value of paramount importance in a well ordered and open society. Following some ideas of John StuartMill, we propose that freedom of choice has to be understood not in a single stage of choice, but in the ordered collection of choices that a person can make in her life.We then suggest to represent a life in a tree structure, where each node represents a state of life and the edges between nodes will represent possible decisions in life. In this new framework, we propose a set of axioms that imply the following family of measures of lifetime's freedom of choice: the lifetime's freedom of choice has to be evaluated by a weighted sum of all possible states of life an individual might visit, with weights representing the number of decisions the individual took to reach that state.
Keywords: D63; D71; 330; freedom of choice; tree of life; autonomy; Freiheit; Lebensverlauf; Entscheidung; Neue politische Ökonomie